RT-lab based real-time simulation of flywheel energy storage system associated to a variable-speed wind generator - Bensaid Amel; Zebirate Soraya; Chaker Abdelkader (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper presents a new simulator used to distribute and execute real-time simulations: the RT-LAB, developed by opal-RT technologies (Montreal, Canada). One of its essential characteristics is the perfect integration with MATLAB/Simulink. The RT-LAB allows the conversion of Simulink models in real time via real-time workshop (RTW) and their execution on one or more processors. In this context, the paper focuses on the RT-LAB real-time simulation as a complement to the MATLAB/Simulink environment, which has been used to perform the simulation of the Flywheel energy storage system (FESS -variable speed wind generation (VSWG) assembly. The purpose of employing a fairly new real-time platform (RT-LAB OP -5600) is to reduce the test and prototype time. This application will be executed on each element of our model that was previously developed under MATLAB/Simulink. The real-time simulation results are observed in the workstation.